Factors influencing student's absenteeism in university level (Universiti Malaysia Sarawak) - Syarifah Suhaila, Bt. Tahir. (Universiti Malaysia Sarawak, 2011)
This study aimed to determine the factors that influencing student's absenteeism in university level. The study was conducted in Universiti Malaysia Sarawak. The dependent variable in this study was student's absenteeism and while the independent variables were demographic characteristics, subject interest, lecturer's skills, student's attitude, and health problems. A survey questionnaires in the form of Likert Scale were used to obtain data from a sample of 120 respondents from four selected faculty, i.e. Faculty of Applied and Creative Arts (F ACA), Faculty of Cognitive Science and Human Development (FCSHD), Faculty of Resource Science and Technology (FRST), and Faculty of Social Sciences (FSS). The data collected was analyzed using descriptive statistic and inferential statistic. Percentages and frequencies were used to determine the distribution of the demographic characteristics. T -test was used to determine the significant difference between male and female students in term of their perceived absenteeism (t = -1.280, df = 118, p= 0.203) showed that p value was bigger than 0.05.The result indicated that there is no significant difference between male and female students in terms' of students' absenteeism. Pearson Correlation test was used to determine the significant relationship between factors of subject interest(r= 0.421, p= 0.000), lecturer's skills(r= 0.549, p= 0.000), student's attitude(r= 0.426, p= 0.000), and health problems (r= 0.221, p= 0.015) toward absenteeism. The finding of this study showed that there was a significant relationship between factors of subject interest, lecturer's skills, student's attitude, and health problems towards absenteeism. Based on the study, lecturer's skills was the most dominant factor that influenced student's absenteeism. This study would contribute to enhance the knowledge and understanding of absenteeism in the university.